PROFIL EPITHELIAL OVARIAN CARCINOMA (EOC) DI DR. RUMAH SAKIT UMUM KARIADI SEMARANG - Arianto, Adi; Istiadi, Hermawan; Puspasari, Dik (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2021)
Ovarian cancer is the 7th leading cancer in incidence (3,4%) after breast, colorectal, lung, cervix uteri, thyroid, corpus uteri and stomach cancer among women worldwide according to Globocan, 2018. Ovarian cancer in Indonesia is the 3rdmost leading cause of cancer death, after cervix and breast cancer. The most common type of ovarian cancer is epithelial ovarian carcinoma (EOC), which most prevalent in older women. This study was aimed to describe clinicopathological profile of EOC in kariadi general hospital semarang from January 2016 to December 2018. This is the observational analytical studyusing data of ovarian cancer patient medical records at the laboratory of pathological anatomy in kariadi general hospital semarang. Data collection include : age of diagnosis, location, size tumor and histological subtype. 330 EOC patient were included in this study. Most of EOC patient (52%) were diagnosed more than 40 years old. 81% of EOC patient had unilateral location. 60% of patient had size tumor more than 14 cm in diameter. Histological subtype of patient was mostly mucinous carcinoma (40%). EOC patient in kariadi general hospital semarang was mostly diagnosed at more than 40 y.o, had unilateral location and had mucinous carcinoma subtype.